Cavalo do Vingador: Ethos da garimpagem na fronteira da Amazônia franco-brasileira – uma análise sociológica em Oiapoque - Fonseca, Gladson Paulo Milhomens (2020)
The present work analyzes the culture and experiences of mining in the Amazonian border between Brazil and French Guiana. The research is based on the empirical analysis of experiences made up of different groups and their respective forms of sociability found at the border. It is argued that this relationship of proximity, as noted, is imbued with a local Ethos, capable of aggregating different modes of sociability immersed in its socio-economic constitution, whose referential bases are linked to the clandestine mines of Guyana territory. Over the decades, northern Amapá became the central focus of the gold rush in Guyanese lands as the main economic reference in Oiapoque, excluded from informal gold exploration networks. The methodological choice was based on participant observation (through direct / indirect contacts) with the existing social groups and interviews conducted from the circumstantial context of men and women linked in their different forms to the gold mining universe experienced in clandestine areas of French Guiana. In general, it is understood that mineral extraction is part of the historical, social and economic constitution of the Brazilian Amazon. In any case, the frontier cannot be thought of as a compact space, but as a disruption, a place capable of neutralizing the institutional functions of the State, creating forms of peculiar sociability, capable of operating through the ways of informality in its most varied practices.